2015
DOI: 10.1016/j.physc.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

On the room-temperature aging effects in YBa 2 Cu 3 O 6+δ

Abstract: a b s t r a c tThe aging effects in YBa 2 Cu 3 O 6+d have been investigated on the low-speed quenched samples in contrast to other similar studies where the high-speed quenched samples were examined. In the framework of the investigation, XPS analysis has been conducted for the samples stored after quenching for the specified times s and a detailed experimental dependence of the YBa 2 Cu 3 O 6+d lattice parameters a, b, and c on both d and s has been obtained. The regime of low-speed quenching results in a thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
4
14
1
Order By: Relevance
“…One can state that the YBCO phase is rather contracted after exposure to air. The lattice parameters of exposed YBCO correspond to the maximally oxidized state of YBCO [9]. On the other hand, our study has not revealed radical changes in the structure that would be evidence of the transformation of YBCO under the action of absorbed water into the pseudo-YBa 2 Cu 4 O 8 phase, as had been observed in [10], or into another phase.…”
Section: Characterization Of the Initial And Hydrated Ybco By Xrd Andsupporting
confidence: 46%
“…One can state that the YBCO phase is rather contracted after exposure to air. The lattice parameters of exposed YBCO correspond to the maximally oxidized state of YBCO [9]. On the other hand, our study has not revealed radical changes in the structure that would be evidence of the transformation of YBCO under the action of absorbed water into the pseudo-YBa 2 Cu 4 O 8 phase, as had been observed in [10], or into another phase.…”
Section: Characterization Of the Initial And Hydrated Ybco By Xrd Andsupporting
confidence: 46%
“…phases, occurring in Nd-123ss at   6.6 [13]. Meanwhile, the  dependence of these parameters is rather weak compared to the same dependence of c. It corroborates the result of [4] on the influence of charge in the CuO 2 planes namely on the distance between structural layers, that is reflected in equation (1).…”
Section: Methodssupporting
confidence: 80%
“…To obtain samples with different oxygen content, additional annealing in air at temperatures of the range 470-940C following by quenching was conducted. More detailed information on this procedure is contained in [4]. The oxygen content was monitored by the change in mass of the sample during additional 1 h -oxidation at 470 C in air, counting on this treating to give rise to (6+) = 6.953 [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations